Fructose modifies the hormonal response and modulates lipid metabolism in aerobic exercise after glucose supplementation - Fernández, Juan Marcelo; da Silva-Grigoletto, Marzo Edir; Ruano-Ruiz, Juan; Caballero-Villarraso, Javier; Moreno-Luna, Rafael; Tunez-Fiñana, Isaac; Tasset-Cuevas, Inmaculada; Pérez-Martinez, Pablo; López-Miranda, José; Pérez-Jiménez, Francisco (Clinical science (1979), 2008)
The metabolic response, when aerobic exercise is performed after the ingestion of glucose plus fructose, is unclear. To compare the hormonal and lipid responses provoked by the ingestion of glucose plus fructose in relation to glucose alone, during aerobic exercise and the recovery phase, we administered two beverages containing glucose plus fructose or glucose in a randomised crossover design, to twenty healthy, aerobically trained volunteers. After a 15-minute resting period they performed 30 minutes of moderate aerobic exercise. Urinary and blood samples were taken at baseline (t-15), during the exercise (t0; t15; t30) and during the recovery phase (t45; t75; t105). Plasma insulin concentrations were higher half-way through the exercise period and during acute recuperation (t15 and t75; p<0.05) following ingestion of glucose plus fructose than after glucose alone, without any differences between the effects of either intervention on plasma glucose concentrations. Towards the end of the exercise, urinary catecholamine concentrations were lower following glucose plus fructose (t45; p<0.05). Plasma triglyceride concentrations were higher after the ingestion of glucose plus fructose than after glucose (t15; t30; t45; t105; p<0.05). Furthermore, with glucose plus fructose we found higher levels of lipoperoxides (t15; t30; t45; t105; p<0.05) and oxidised LDL (t30; p<0.05) than after the ingestion of glucose alone. In conclusion, hormonal and lipid alterations are provoked during aerobic exercise and recovery, by the addition of a dose of fructose to the pre-exercise ingestion of glucose.